The effect of basic carbohydrate counting on hba1c in type 2 diabetic patients: a non-randomized controlled trial - UZUNER, ARZU; CÖBEK ÜNALAN, GÜLRU PEMRA (My University, 2022)
Background:Carbohydrate counting (CC) is considered as a medical nutrition therapy method especially used in Type 1DM (T1DM) patients in basic and advanced levels. Limited number of studies reported that basic CCimproves glycemic control in T2DM patients, and there is need for further studies.Research questions:How the basic CC effects HbA1c levels in T2DM patients using oral antidiabetic drugs, when presented as acomponent of nutrition education by primary care physicians.Method:The study hereby is a non-randomized controlled clinical trial. T2DM patients, aged between 18-75 years,HbA1c levels between 6.5%-10.8% using oral antidiabetic medication, were followed for three months in twogroups; one intervention (IG) (n=33) and one control group (CG) (n=45), in two different Primary CareCenters. General diabetes monitoring principles were applied in both groups; basic CC training was givenadditionally to the IG. The training consisted of three sessions lasting 40 minutes each. An informative CCbooklet was provided to both groups. Beside sociodemographic questionnaire, a healthy nutrition informationscale was applied to all of the participants; HbA1c, other laboratory and anthropometric measurements wereperformed at the beginning and at the 3rd month of the study.Results:The mean age value was 54.58±9.69 (28-73). Male/female distribution was (IG:57.6%/42,4%,CG:53.3%/46,7%). At the third month, HbA1c value decreased within the IG from 7.7% to 7.2% (p:0.002),from 7.49% to 7.46%, in the CG (p:0.851). Comparing two groups, the decrease in HbA1c in the IG washigher than in the CG (-0.5, -0.02, p: 0.018). Third month knowledge score was higher the intervention group’s(<0.001).Conclusions:Basic CC training provided to T2DM patients by primary care physician, improves glycemic control byincreasing CC knowledge level and improving HbA1c.Points for discussion:How to integrate basic CC education at the diabetes management primary care centers?Presentation on 13/05/2022 16:30 in \"Parallel Session G - Theme Papers: Diabetes\" by Hamide Vural.
Keywords: Tıp; Dahili Tıp Bilimleri; Aile Hekimliği; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Family Medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; SAĞLIK BAKIM BİLİMLERİ VE HİZMETLERİ; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; HEALTH CARE SCIENCES & SERVICES; MEDICINE, GENERAL & INTERNAL; Tıbbi Terminoloji; Tıbbi Sekreterlik ve Transkripsiyon; Sağlık Bilgi Yönetimi; Sağlık Meslekleri (çeşitli); Genel Sağlık Meslekleri; Gözden Geçirme ve Sınav Hazırlığı; Patofizyoloji; Liderlik ve Yönetim; Temel Bilgi ve Beceriler; Toplum Sağlığı ve Evde Bakım; Bakım Planlaması; Değerlendirme ve Teşhis; Dahiliye; Sağlık Politikaları; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; Medical Terminology; Medical Assisting and Transcription; Health Information Management; Health Professions (miscellaneous); General Health Professions; Review and Exam Preparation; Pathophysiology; Leadership and Management; Fundamentals and Skills; Community and Home Care; Care Planning; Assessment and Diagnosis; Internal Medicine; Health Policy; Family Practice; Medicine (miscellaneous); General Medicine